2007
DOI: 10.1080/03601230701465882
|View full text |Cite
|
Sign up to set email alerts
|

Residues of organochlorine pesticides and PCBs in some Brazilian municipal solid waste compost

Abstract: Persistent organic pollutants (POPs), organochlorine pesticides and polychlorinated biphenyls (PCBs), listed as per the Stockholm Convention (alpha -HCH, beta -HCH, gamma -HCH, p,p'-DDT, o,p'-DDT, p,p'-DDD, p,p'-DDE, aldrin, endrin, dieldrin, PCBs 28, 52, 118, 138, 153, and 180), were analyzed in municipal solid waste (MSW) compost samples from three different Brazilian composting plants located in three São Paulo State cities: Araras, Araraquara and São Paulo (Vila Leopoldinha). Quantitative and qualitative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
1
1
1
Order By: Relevance
“…It is thought that sources of exposure to these pollutants may be both from recent and past activities. It is common practice in Brazil to use municipal solid waste as compost to enrich the soil for agricultural use; it is very possible that this practice has led to overall increase in levels of pollutants in soil, groundwater and in plants, consequently contributing to human exposure (Lourencetti et al, 2007). This study also confirmed that the body burden of selected POPs increases with age and decreases with parity in accordance with other studies (Grimvall et al, 1997;O'Grady Milbrath et al, 2009;Skaare and Polder, 1990).…”
Section: Discussionsupporting
confidence: 90%
“…It is thought that sources of exposure to these pollutants may be both from recent and past activities. It is common practice in Brazil to use municipal solid waste as compost to enrich the soil for agricultural use; it is very possible that this practice has led to overall increase in levels of pollutants in soil, groundwater and in plants, consequently contributing to human exposure (Lourencetti et al, 2007). This study also confirmed that the body burden of selected POPs increases with age and decreases with parity in accordance with other studies (Grimvall et al, 1997;O'Grady Milbrath et al, 2009;Skaare and Polder, 1990).…”
Section: Discussionsupporting
confidence: 90%
“…In Brazil, it is common practice to use municipal solid waste as compost to enrich the soil for agricultural use; it is very possible that this custom has led to increased levels of pollutants in soil, groundwater and in plants, with a concomitant exposure to humans. 38 Even though our study found generally low levels of POPs in delivering women, it is well known that chronic exposure to low levels of POPs, over an extended period of time, can lead to cumulative adverse health effects in exposed populations. 39 To the best of our knowledge, this pilot study is the first Brazilian investigation that concurrently measured a wide spectrum of POPs in whole blood of delivering women, in selected areas of São Paulo State, Brazil.…”
Section: Discussioncontrasting
confidence: 54%
“…Switzerland (Brandli et al, 2007). The contents of persistent organic pollutants, organochlorine pesticides and polychlorinated biphenyl in municipal solid waste compost samples from three different Brazilian composting plants were studied by Lourencetti et al (2007). The results suggested that municipal solid waste compost used for agricultural purposes should be evaluated and controlled.…”
mentioning
confidence: 99%